2009
DOI: 10.1021/jf901381x
|View full text |Cite
|
Sign up to set email alerts
|

Some Phenolic Compounds Increase the Nitric Oxide Level in Endothelial Cells in Vitro

Abstract: The vasorelaxing properties of chocolate and wine might relate to the presence of phenolic compounds. One of the potential mechanisms involved is stimulation of endothelial nitric oxide (NO) production, as NO is a major regulator of vasodilatation. This study aimed to develop an in vitro assay using the hybrid human endothelial cell line EA.hy926 to rapidly screen phenolic compounds for their NO-stimulating potential. The assay was optimized, and a selection of 33 phenolics, namely, procyanidins, monomeric fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 36 publications
5
51
0
1
Order By: Relevance
“…Similarly, other studies confirmed that high concentrations of resveratrol significantly enhanced eNOS gene expression and enzyme activity, and hence NO production, in in vitro assays (Räthel et al, 2007;Appeldoorn et al, 2009). In contrast, Nicholson et al (Nicholson et al, 2010) reported that exposure of HUVECs to nanomolar concentrations of resveratrol for 24 h increased the eNOS mRNA level, although eNOS protein and NO production were not affected.…”
Section: Effects Of Resveratrol On Antioxidant Mechanisms Protecting mentioning
confidence: 53%
“…Similarly, other studies confirmed that high concentrations of resveratrol significantly enhanced eNOS gene expression and enzyme activity, and hence NO production, in in vitro assays (Räthel et al, 2007;Appeldoorn et al, 2009). In contrast, Nicholson et al (Nicholson et al, 2010) reported that exposure of HUVECs to nanomolar concentrations of resveratrol for 24 h increased the eNOS mRNA level, although eNOS protein and NO production were not affected.…”
Section: Effects Of Resveratrol On Antioxidant Mechanisms Protecting mentioning
confidence: 53%
“…Punicalagin and o-galloyl punicalagin extracted from Terminalia calamansanai plant leaves (50 µM each) produced a significant increase in NO production in bovine aortic cell line [41]. NO production was also significantly increased in a dose-dependent manner after incubating the EA.hy926 cell line for 24 hours with different polyphenols (resveratrol, epicatechin gallate and epigallocatechin gallate) [42]. Different concentrations (0.1-10 µM) of polyphenols extracted with 70 % acetone from black currant were exposed to EA.hy926 cell line for 10 minutes and produced a significant increase in NO productionin a dose-dependent manner [36].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of resveratrol, epigallocatechingallate and epicatechingallate on eNOS enzyme was investigated on EA.hy926 cell line at different concentrations (0-100 µM) for 24 hours. The protein level of eNOS enzyme was significantly increased in a dose dependent manner [42]. Edirisinghe et al, (2011) studied the black currant polyphenols 70% acetone extract on protein expression of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…71) However, their experiments were not conducted under dietary conditions, as the biological activity of resveratrol was observed between 10 and 100 μM. Räthel et al 82) and Appeldoorn et al 83) confirmed that resveratrol at high concentrations significantly enhanced eNOS gene expression and enzyme activity, and NO production. In contrast, Nicholson et al 84) reported that the exposure of HUVECs to nanomolar concentrations of resveratrol for 24 h increased the eNOS mRNA level, although neither eNOS protein nor NO production were determined.…”
Section: Link To Enosmentioning
confidence: 99%